2017
DOI: 10.3341/kjo.2016.0125
|View full text |Cite
|
Sign up to set email alerts
|

Five-year Outcomes of Ranibizumab in Neovascular Age-related Macular Degeneration: Real Life Clinical Experience

Abstract: PurposeTo evaluate the outcomes of 5-year ranibizumab treatment in neovascular age-related macular degeneration (nAMD) in a single center and real life clinical setting.MethodsThe records of nAMD patients who were treated with ranibizumab between January 2010 and June 2011 were retrospectively reviewed. Patients who completed 5 years of follow-up were included. Main outcome measures were change in best-corrected visual acuity, central retinal thickness, and visit and injection numbers.ResultsForty-four eyes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Improvements of BCVA were associated with significant reductions of CSFT and CSV in each study arm, without differences among the treatment regimens used. These findings are consistent with a large body of evidence of the efficacy of ranibizumab in nAMD reported in the literature (Rosenfeld et al 2006;Brown et al 2009; Comparison of Age-Related Macular Degeneration Treatment Trials (CATT) Research Group 2016; Vardarinos et al 2017;Ozkaya et al 2017;Silva et al 2017;Guo et al 2018). However, to the best of our knowledge, this is the first prospective randomized trial comparing the clinical efficacy and safety of three regimens, bimonthly, T&E and PRN in treatment-na€ ıve patients with nAMD.…”
Section: Discussionsupporting
confidence: 89%
“…Improvements of BCVA were associated with significant reductions of CSFT and CSV in each study arm, without differences among the treatment regimens used. These findings are consistent with a large body of evidence of the efficacy of ranibizumab in nAMD reported in the literature (Rosenfeld et al 2006;Brown et al 2009; Comparison of Age-Related Macular Degeneration Treatment Trials (CATT) Research Group 2016; Vardarinos et al 2017;Ozkaya et al 2017;Silva et al 2017;Guo et al 2018). However, to the best of our knowledge, this is the first prospective randomized trial comparing the clinical efficacy and safety of three regimens, bimonthly, T&E and PRN in treatment-na€ ıve patients with nAMD.…”
Section: Discussionsupporting
confidence: 89%
“…31 In studies continuing beyond 3 years, declining VA with anti-VEGF PRN regimens was observed over the long term. [34][35][36][37][38][39][40][41][42] Furthermore, in a small study in which initial VA gains were maintained for up to 5 years, the number of injections administered annually increased in later years (median of seven injections in Year 5 vs four injections in Years 2-4). 43 This observation is consistent with other studies that indicated that, despite treatment being administered on a PRN basis, a higher number of injections is independently correlated with improved VA for patients with nAMD treated with ranibizumab.…”
Section: Anti-vegf Treatment In Pro Re Nata (Prn; As Needed) Regimensmentioning
confidence: 99%
“… 8 Numerous studies were conducted to reevaluate the outcomes of this treatment regimen. 6 , 8 , 11 , 12 Physicians liked the idea of seeing the patients every month and injecting when required, because the PRN regimen seemed to have the advantage of individualized dosing. 8 However, most of the subsequently published real-world practice studies revealed that it was not possible to obey the strict follow-up and retreatment criteria of randomized controlled trials in daily practice.…”
Section: Introductionmentioning
confidence: 99%
“… 8 However, most of the subsequently published real-world practice studies revealed that it was not possible to obey the strict follow-up and retreatment criteria of randomized controlled trials in daily practice. 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Most of these studies showed that the PRN regimen resulted in less frequent patient monitoring and injections. Several single-center and multicenter national studies were conducted to evaluate this phenomenon.…”
Section: Introductionmentioning
confidence: 99%